Study the Growth Curve for AMN-3 Cell Line - Maeda H. Mohammad; Hussamelden M. Kadhum; Ahmed M. AL- Shamery; Aymen A. Hassan (Iraqi Journal of Cancer and Medical Genetics, 2010)
Tissue culture technique was used to study the growth carve for AMN-3 cell line witch had been grown in vitro for three different passages (114, 118, 123), five sequenced between one passage to other and for ten period (12, 24, 36, 48, 60, 72, 84, 96, 108, 120) hour; to detects the stages of cell cycle and calculate population doubling time (PDT) for three passages. The result show the shorten of the Lag phase(from zero point- 12) h. for three passages in comparison to other stages, in the other side the long in the Log phase, its between 12- 72 hour for the passages 123, 114 and 12- 60 hour for 118 passage. The variation of population doubling time for the three passages was reaches sequins 21.34, 19.94 and 20.54 hour. Thus the result was show adhesions between Log and Stationary phase until the decline phase which show redacts in among cell growth during the time until 120 h. of the study and for the three passages